2019
DOI: 10.1002/jcla.22974
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of metal toxicity in embryos in the general population

Abstract: BackgroundWith the development of industrialization, public exposure to toxic metals could occur everywhere, eventually affecting individuals’ reproductive systems and even embryos and leading to early pregnancy loss. The aim of the study was to determine the profile of toxic metal levels in pregnant women in the general population and to identify biomarkers for metal toxicity in embryos.MethodsA case‐control study with pregnant women was conducted at Peking Union Medical College Hospital in 2016‐2018. Women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The odds ratios for spontaneous abortion in five blood lead levels (5–9, 10–14, 15–24, 25–39, and ≥40 μg/L) were 1.58 (0.23–10.90), 3.13 (2.11–9.08), 4.63 (1.45–14.83), 6.33 (1.95–20.56), and 22.56 (4.91–103.66), respectively, indicative of a significant trend (P1 = 0.64, P2 = 0.02, P3 = 0.01, P4 = 0.02, and P5 = 0.00) ( 38 ). Yildrim and Derici ( 42 ) found higher blood Pb levels ( p = 0.038) in pregnant women with history of spontaneous abortion compared to control ( 43 ), while the study by Turan et al ( 43 ) showed significantly increased ( p < 0.001) serum concentrations of Pb and Cd in women with threatened abortion compared to control ( 44 ). Jie et al ( 41 ) demonstrated that blood cadmium >0.4 µg/L or urine chromium >2 µg/L in pregnant women was indicative of a higher risk of spontaneous abortion ( 42 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The odds ratios for spontaneous abortion in five blood lead levels (5–9, 10–14, 15–24, 25–39, and ≥40 μg/L) were 1.58 (0.23–10.90), 3.13 (2.11–9.08), 4.63 (1.45–14.83), 6.33 (1.95–20.56), and 22.56 (4.91–103.66), respectively, indicative of a significant trend (P1 = 0.64, P2 = 0.02, P3 = 0.01, P4 = 0.02, and P5 = 0.00) ( 38 ). Yildrim and Derici ( 42 ) found higher blood Pb levels ( p = 0.038) in pregnant women with history of spontaneous abortion compared to control ( 43 ), while the study by Turan et al ( 43 ) showed significantly increased ( p < 0.001) serum concentrations of Pb and Cd in women with threatened abortion compared to control ( 44 ). Jie et al ( 41 ) demonstrated that blood cadmium >0.4 µg/L or urine chromium >2 µg/L in pregnant women was indicative of a higher risk of spontaneous abortion ( 42 ).…”
Section: Discussionmentioning
confidence: 95%
“…Out of 30 eligible articles included in the present systematic review, 16 articles focused on clinical studies investigating IVF outcomes (Table 1) (16, 21-35) while 14 articles focused on clinical studies that investigated reproductive concerns (Table 2) (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…42% of children below five years, 50% of pregnant women-, and 33% women of reproductive age are iron deficient worldwide. 37,38 Among women with miscarriages, 13% higher serum iron levels are seen in 14 weeks of pregnancy. In support of the above findings, serum hepcidin and ferritin concentrations were higher in the first trimester due to possible accumulation of iron in maternal serum because the fetus is not receiving maternal iron through the placenta leading to SA.…”
Section: Ironmentioning
confidence: 99%